ASSESSMENT MODEL FOR DETERMINING SOIL ERODIBILITY FACTOR IN LOMBOK ISLAND - Muhammad Rahman Djuwansah; Asep Mulyono (Indonesian Institute of Sciences, 2017)
One of soil parameters that affects the rate of erosion is the soil erodibility. Soil erodibility studies had been conducted in one of the watershed of Lombok in 2015. The tests were carried out for five soil profiles by taking samples from each layers. Samples were analyzed for particles sizes and organic matter contents. The analysis was performed using two assessment models of soil erodibility, the Universal Soil Loss Equation (USLE) and Erosion Productivity Impact Calculator (EPIC) models. Obtained soil erodibility (K factors) values varied from 0.07 to 0.74 for USLE models and 0.18 to 0.46 for EPIC models. Statistical similarity (R) test resulted R=-0.28*10-19. It has indicated that there was no statistical difference between the results of both methods. The older volcanic rocks give a high erodibility factor. In this study, vertisols soils show a higher erodibility factor than other volcanic rocks, such as inceptisols, andisols and entisols soil. Lower soil organic matter and clay contents are the factors that influence high soil erodibility.Salah satu parameter tanah yang sangat berpengaruh terhadap besarnya erosi adalah faktor erodibilitas tanah. Studi erodibilitas tanah telah dilakukan di salah satu DAS di Pulau Lombok dengan uji lapangan. Uji lapangan dilakukan pada 5 profil tanah dan pengambilan sampel pada setiap lapisan untuk uji laboratorium terhadap kandungan partikel pasir, debu, liat dan bahan organik tanah. Analisis dilakukan menggunakan 2 model prediksi erodibilitas tanah yaitu model Universal Soil Loss Equation (USLE) dan Erosion Productivity Impact Calculator (EPIC). Nilai erodibilitas tanah dengan model USLE berkisar 0.07-0.74 dan 0.18-0.46 dengan model EPIC. Analisis statistik dengan tes R menghasilkan R=-0,28*10-19 yang menandakan nilai K yang diperoleh oleh kedua metode tidak berbeda. Endapan batuan vulkanik yang lebih tua di wilayah studi menghasilkan tingkat erodibilitas yang tinggi. Jenis tanah vertisols yang berasal dari endapan batuan volkanik tua menghasilkan tingkat erodibilitas tanah yang lebih tinggi dibandingkan jenis tanah lain yang terbentuk dari endapan batuan vulkanik seperti tanah inceptisols, andisols dan entisols. Semakin rendahnya kandungan bahan organik dan liat dalam tanah mengakibatkan semakin tingginya erodibilitas tanah.